An Analysis on Hybridization in Arabi Malayalam - Saidalavi Cheerangote (International Review of Social Sciences and Humanities, 2012)
This paper is based on a small-scale study on the degree of hybridization in Arabi Malayalam language with special reference to “Bettilappattu” and “Uhdupadappattu”, Arabi Malayalam works of Moyeenkutty Vaidyar. The study evaluates the linguistic data obtained from the literary works. Findings indicate that among the loan words, the frequency of Arabic words and Arabi Malayalam compounds are higher. It also analyzes the peculiarities of noun suffixes and identifies the grammatical features that contradict the standard Malayalam grammar. The findings can be useful in gaining a better understanding of the phenomenon of hybridization aspect in contact language situation and brings in new information based on the linguistic investigation done.